Enhancing Non-Formal Early Childhood Teachers’ Competence through Digital Learning Media Development - Novita, Sophia; Darmawan, Ferry; Hakim, Arif; Aqilah, Halimah; Hildayanti, Widia Helti; Alviano, Riko (UPT Publikasi Ilmiah UNISBA, 2026)
Early Childhood Education (PAUD) plays a vital role in developing children’s character, social skills, and readiness to learn. However, many non-formal PAUD institutions in Indonesia face challenges in adopting digital technology due to limited resources, inadequate infrastructure, and teachers’ limited digital competence. This community service aimed to enhance teachers’ competence in developing digital learning media in Andir District, Bandung, through a participatory training program. A total of 19 educators participated in activities, including a pre-test, workshops, hands-on practice, and a post-test. The training introduced accessible tools, including ChatGPT, Canva, PowerPoint, and Sound of Text, to support the creation of interactive learning media.The results show a substantial improvement in participants’ competence. The average score increased from 34.38% in the pre-test to 94.08% in the post-test, indicating an improvement of 59.70%. In terms of practical skills, none of the participants were able to develop interactive learning media before the training. In contrast, all participants (100%) successfully produced more than three interactive learning media products after the training.These findings suggest that practical, context-based digital training with accessible tools can effectively enhance teachers’ competence in developing digital learning media in non-formal early childhood education